A clinical evaluation of the performance of five commercial artificial intelligence contouring systems for radiotherapy - Doolan, Paul J.; Charalambous, Stefanie; Roussakis, Yiannis; Leczynski, Agnes; Peratikou, Mary; Benjamin, Melka; Ferentinos, Konstantinos; Strouthos, Iosif; Zamboglou, Constantinos; Karagiannis, Efstratios (Frontiers in Oncology, 2023)
PURPOSE/OBJECTIVE(S): Auto-segmentation with artificial intelligence (AI) offers an opportunity to reduce inter-and intra-observer variability in contouring, to improve the quality of contours, as well as to reduce the time taken to conduct this manual task. In this work we benchmark the AI autosegmentation contours produced by five commercial vendors against a common dataset.METHODS AND MATERIALS: The organ at risk (OAR) contours generated by five commercial AI auto-segmentation solutions (Mirada (Mir), MVision (MV), Radformation (Rad), RayStation (Ray) and TheraPanacea (Ther)) were compared to manually-drawn expert contours from 20 breast, 20 head and neck, 20 lung and 20 prostate patients. Comparisons were made using geometric similarity metrics including volumetric and surface Dice similarity coefficient (vDSC and sDSC), Hausdorff distance (HD) and Added Path Length (APL). To assess the time saved, the time taken to manually draw the expert contours, as well as the time to correct the AI contours, were recorded. RESULTS: There are differences in the number of CT contours offered by each AI autosegmentation solution at the time of the study (Mir 99; MV 143; Rad 83; Ray 67; Ther 86), with all offering contours of some lymph node levels as well as OARs. Averaged across all structures, the median vDSCs were good for all systems and compared favourably with existing literature: Mir 0.82; MV 0.88; Rad 0.86; Ray 0.87; Ther 0.88. All systems offer substantial time savings, ranging between: breast 14-20 mins; head and neck 74-93 mins; lung 20-26 mins; prostate 35-42 mins. The time saved, averaged across all structures, was similar for all systems: Mir 39.8 mins; MV 43.6 mins; Rad 36.6 min; Ray 43.2 mins; Ther 45.2 mins.CONCLUSIONS: All five commercial AI auto-segmentation solutions evaluated in this work offer high quality contours in significantly reduced time compared to manual contouring, and could be used to render the radiotherapy workflow more efficient and standardized.